2022
DOI: 10.1155/2022/3937375
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Construct and Interpretation of Chelated Coordination Polymers and Their Use in Nanomaterials Research

Abstract: Presently, an important step from basic research to practical applications is synthesizing nanostructured materials. Metal-organic structures, as well as coordination polymers, are a diverse group of materials with a wide range of potential and properties applications. It has been difficult to get these materials into commercial use because of many drawbacks. Polymers containing chelated units are described and assessed for their advancements and problems in preparation, properties, and structure. Here, a prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%